Directive Illocutionary Acts with Special Reference to Pitch Perfect - Kurnia Utami, Putu (Humanis, 2018)
Abstract The current study entitled Directive Illocutionary Acts with Special Reference to Pitch Perfect aims to analyze the type of the modes of utterance and the forces of the illocutionary acts found in the Pitch Perfect movie. The current study used the dialogues taken from the Pitch Perfect movie as the data. First, the movie was watched and the script was downloaded. While reading the script, the potential data were noted. Furthermore, the data were selected and the relevant ones were analyzed. The data were analyzed using two main theories; the speech act theory by John R. Searle (1969) and the theory of context of situation proposed by Halliday (1989). The theory proposed by John R. Searle was used to identify whether or not the data were directives illocutionary acts. In addition, the theory proposed by Halliday was used to analyze the forces of the modes of utterances.Based on the analysis, it was found that directives illocutionary acts could be performed in three modes; declarative, interrogative and imperative under the dictum “I want you to do something”. There were ten data in declarative mode, ten data in interrogative mode and 5 data in imperative mode had been analyzed. The forces of the modes of utterance found were commanding, inviting, requesting, advising and begging.